Stance-taking: reporting verbs in citations in EFL undergraduate theses - Olmos-Lopez, Pamela (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2022)
L2 writers tend to have difficulties in using reporting verbs (Bloch, 2010) because the choosing of reporting verb needs some considerations: the stance of the author whose claims are being reported, the stance of the writer, and the interpretation of the writer (Thompson and Ye, 1991). This article explores stance-taking in reporting verbs in the context of citations in undergraduate theses written by Mexican students in English as a Foreign Language. The corpus consists of thirty undergraduate theses written by non-native speakers of English in the field of English Language Teaching. I use corpus linguistics tools, i.e., concordances for the analysis of stance-taking which makes the expressions observable in their context. The findings show that undergraduates use reporting verbs to express their stance in their theses and that this varies depending on the chapter. This paper suggests a category of reporting verbs that is commonly used in EFL academic writing within the ELT discipline. I propose some educational implications, stressing the need to make students and their instructors aware that the choice of reporting verbs is not just a matter of stylistic choice, but it can be an expression of authorial identity.